From Certification to Compliance: Halal Compliance Rating in Indonesian Restaurants - Inas Afifah Zahra; Mohammad Nur Rianto Al Arif; Muniaty Aisyah; Yuke Rahmawati (ETIKONOMI, 2026)
Research Originality: This study extends halal restaurant research by reframing halal compliance from a binary certification issue into a multidimensional managerial construct. It does so through a Halal Compliance Rating (HCR) framework based on the Indonesian Halal Assurance System (IHAS). Research Objectives: This study aims to measure the importance and performance of implementing IHAS-based HCR in halal restaurants in Indonesia   Research Method: The study applied a cross-sectional survey involving 40 halal-certified restaurants purposively sampled. A structured 20-item questionnaire was developed based on the IHAS and was administered to restaurant operators. The data were then analyzed using Importance Performance Analysis (IPA). Empirical Results: Halal-certified restaurants performed well in operational aspects of halal, including thayyib and halal practices, hygiene, branding, customer trust, and halal supply chains. However, lower ratings were recorded in the human resource, cultural, and sustainability dimensions. Implications: Halal restaurant operators are expected to improve post-certification halal governance by developing staff, incorporating Islamic service values, and adopting sustainability practices. Policy implications point to the halal authorities to strengthen capacity, provision, and monitoring systems, and to ensure substantive compliance. JEL Classification: M14, L66, Z12